2010
DOI: 10.3109/00016489.2010.516012
|View full text |Cite
|
Sign up to set email alerts
|

Duffy antigen receptor for chemokines in laryngeal squamous cell carcinoma as a negative regulator

Abstract: It was found that DARC was expressed in the LSCC samples, with a high expression in 32 of our cases (49.2%), and in lymph node-negative and -positive groups of 24 (72.7%) and 8 cases (25%), respectively (p < 0.01). MVD was (24.75 ± 5.45)/High power field (HP) and (32.58 ± 5.23)/HP in the cases with high and low expression of DARC, respectively (p < 0.01). More importantly, the DARC expression presented a strong negative correlation with nodal metastasis, with pTNM stage, and with recurrence, and the cases with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 19 publications
2
7
0
Order By: Relevance
“…The present study suggested that DARC may inhibit EOC growth and metastasis via an anti-angiogenesis effect. This result is partially consistent with certain previous studies in other types of cancer, including non-small-cell lung cancer (26), breast cancer (13,31,32), thyroid cancer (20) and laryngeal squamous cell carcinoma (33). The inhibitory effect of DARC on ovarian cancer growth and metastasis is mainly due to its ability to sequester pro-malignant chemokines.…”
Section: Discussionsupporting
confidence: 93%
“…The present study suggested that DARC may inhibit EOC growth and metastasis via an anti-angiogenesis effect. This result is partially consistent with certain previous studies in other types of cancer, including non-small-cell lung cancer (26), breast cancer (13,31,32), thyroid cancer (20) and laryngeal squamous cell carcinoma (33). The inhibitory effect of DARC on ovarian cancer growth and metastasis is mainly due to its ability to sequester pro-malignant chemokines.…”
Section: Discussionsupporting
confidence: 93%
“…This finding is of particular interest given that a recent study of three populations of African descent found a relationship between a functional polymorphism in the DARC gene and an increased susceptibility to asthma (59). Moreover, in several types of cancer, increased DARC expression was associated with decreased tumor metastasis and tumor size, as well as higher survival rates (60,61). Our results indicate that the inhibitory effect of CXCL1 is mediated through DARC and suggest that DARC may play a protective role in migration-dependent diseases, such as asthma and cancer.…”
Section: Discussionmentioning
confidence: 87%
“…A protective role of ACKR1 in cancer is also suggested by data obtained with different human tumors. In breast [29,34,35], thyroid [36], colorectal [37], and laryngeal squamous cell [38] tumors, ACKR1 expression was positively correlated with a better outcome, even if the cell types expressing ACKR1 in these samples were not characterized. In summary, these results indicate ACKR1 as a negative regulator of tumor growth.…”
Section: Ackr1/darcmentioning
confidence: 97%